2005
DOI: 10.1002/art.20926
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for musculoskeletal ultrasonography by rheumatologists: Setting global standards for best practice by expert consensus

Abstract: Objective. To establish an expert consensus of best practice for rheumatologists performing musculoskeletal ultrasonography (MUS).Methods. A panel of worldwide experts in MUS was identified by literature review, membership of teaching faculty, and peer recommendation. They were invited to take part in a 4-stage Delphi process employing 2 iterative rounds to establish a consensus of specific indications, anatomic areas, and knowledge and skills required by rheumatologists performing MUS. Results. Experts in MUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 22 publications
2
43
0
4
Order By: Relevance
“…For the purposes of the consensus statement, agreement among the respondents of ≥70% for each statement was considered consensus, according to previous Delphi studies. [13][14][15] The scientific steering committee evaluated the responses and grouped those for which no consensus was reached and that were selected for the following step. After the individual and anonymous online survey, the participants (plus the nine members of the steering committee) attended a meeting to share the results of the first-round voting.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of the consensus statement, agreement among the respondents of ≥70% for each statement was considered consensus, according to previous Delphi studies. [13][14][15] The scientific steering committee evaluated the responses and grouped those for which no consensus was reached and that were selected for the following step. After the individual and anonymous online survey, the participants (plus the nine members of the steering committee) attended a meeting to share the results of the first-round voting.…”
Section: Discussionmentioning
confidence: 99%
“…These have contributed to the development of essential issues, MSUS training method and competency assessment in rheumatology [24][25][26][27][28][29][30][31]. More recently, training in ultrasound-guided injections for rheumatologists among countries has been tested and results demonstrated that the percentage of rheumatologists receiving training in the field is <10% in over 70% of countries that participated in the survey [32].…”
Section: Education and Training In Msusmentioning
confidence: 99%
“…, Sectional anatomy , US physics and technology , Joint US scanning method , US pattern of normal musculoskeletal tissues , Pathological MSUS findings , MSUS artefacts , MSUS diagnostic criteria , Doppler technique , Documentation and report of US findings Later on, Brown et al produced an international interdisciplinary consensus on the specific indications, anatomic areas and knowledge and skills required by rheumatologists performing MSUS [27,28].…”
Section: Box 1 Knowledge and Skills Necessary To Perform Musculoskelementioning
confidence: 99%
“…Some guidelines have been published on the use of MSUS in rheumatology [1][2][3][4][5][6], and some European countries have already incorporated MSUS into the rheumatology training curriculum and have developed training programs for MSUS [7,8]. It is not well known, however, how often Japanese rheumatologists currently use MSUS or how they are currently being trained in the technique.…”
Section: Introductionmentioning
confidence: 99%